Training the aerobic capacity of distance runners: A break from tradition - Turner, A. N. (Strength and Conditioning Journal, 2011)
Aerobic capacity is determined by 3 factors: (a) maximal oxygen uptake, (b) lactate threshold (lt), and (c) running economy (re), and each one should be targeted to optimize development. It appears that vo2max and lt can be adapted simultaneously and may be best trained through high-intensity intervals. Re may be best developed through strength, power, and plyometrics training. Finally, replacing one-third of the total endurance training time with gym-based training appears most beneficial.